The zoomorphic image of St. Christopher on the northern altar doors from the second half of the 16th to early 18th century - Naydyonova, Darya V. (Actual Problems of Theory and History of Art, 2012)
The image of St. Christopher on the northern altar doors is rather rare and unusual phenomenon in the history of Russian painting and in gate decoration as a whole. Th e depiction of the martyr showed an example of repentance on the threshold of Paradise, as soon as the side altar gate reminded of the closed door of Heaven and of the diffi culty in regaining the access there. St. Christopher’s depictions symbolically replaced earlier multiple subjects on the altar doors and were a symbolical substitute for the image of the Penitent robber – another popular character in the decoration of the northern side gates up to the 19th century.